ANALYSIS OF MSME COMPETITIVE STRATEGIES IN FACING DIGITAL COMPETITION - Hendri Mauliansyah (GREET, 2024)
This article aims to analyze the competitive strategies implemented by Micro, Small, and Medium Enterprises (MSMEs) in facing the challenges of digital competition. Using a descriptive qualitative approach, this research is based on literature studies and case study analyses from various reliable sources. This approach enables a deeper understanding of strategies such as cost leadership, differentiation, and market focus used by MSMEs to enhance their competitiveness in the digital era. The analysis was conducted using the SWOT framework and Porter’s Five Forces to evaluate internal and external factors influencing the success of MSMEs. The results of the study indicate that MSMEs that are able to leverage digital technology, understand the market specifically, and maintain service quality tend to be more adaptive and highly competitive. This study also highlights the importance of digital training, technology investment, and data-driven marketing strategies as keys to success in the digital market. These findings are expected to serve as a reference for MSMEs and stakeholders in designing more relevant policies or development strategies in the future.